2018
DOI: 10.26710/jbsee.v4i2.506
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Managers’ Intention to Hire Older Workers

Abstract: The study tested a modified Theory of Planned Behaviour model with an added variable of past experience to predict managers' intention to hire older workers. Surveyed locations were the western coast of Peninsular Malaysia. A cross-sectional data was collected via personal administered questionnaires surveys (n=468). A response rate of 78% (M=59.6%; F=40.4%) was recorded. Models and hypotheses testing were performed using SEM-PLS. Values from internal consistency reliability tests indicated all values were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…In this present study, managers from older-age groups had a more positive attitude towards older workers, as opposed to managers from a young-age group, and the influence of such positivity on the intention to hire supported earlier studies (e.g. Hassell & Perrewe, 1995;Lau et al, 2018). In that sense, managers were more likely to hire or retain older workers in their organizations.…”
Section: 2supporting
confidence: 88%
See 2 more Smart Citations
“…In this present study, managers from older-age groups had a more positive attitude towards older workers, as opposed to managers from a young-age group, and the influence of such positivity on the intention to hire supported earlier studies (e.g. Hassell & Perrewe, 1995;Lau et al, 2018). In that sense, managers were more likely to hire or retain older workers in their organizations.…”
Section: 2supporting
confidence: 88%
“…Paswan, Gai, & Jeon, 2015); intention to hire workers (e.g. Ang, Ramayah & Amin, 2015;Fraser, Ajzen, Johnson, Hebert & Chan, 2011;Lau, Choong & Wong, 2018;Lu & Kao, 2010); intention to retain workers (e.g. Salah, & Habtoor, 2015).…”
Section: Literature Review 21mentioning
confidence: 99%
See 1 more Smart Citation
“…The research findings corroborated with Ang et al (2015) in those managers' attitudes, subjective norm and perceived behavioural control are strong predictors and significant contributors to the prediction of hiring. Additionally, the subjective norm in this present study also supported Lau et al (2018) and Lu et al (2011) where subjective norm was found to be of greatest importance to the intention prediction.…”
Section: The Study Outcomessupporting
confidence: 82%
“…From the various extensive studies on the causal relationship between attitude and behavioural intention indicated that attitude is the best predictor of a behavioural intention (e.g. Earl et al, 2017;Karpinska et al, 2013;Lau et al, 2018;Lu et al, 2011;Ng & Feldman, 2013). The present study defined attitude as favourable or unfavourable consequences of managers in their hiring of older workers.…”
Section: Development Of Hypothesesmentioning
confidence: 81%